Who Receives Specialist Palliative Care in Western Australia - and Who Misses Out - McNamara, B.; Rosenwax, Lorna; Holman, C.; Nightingale, E. (The University of Western Australia, 2004)
Our research describes the provision of palliative care services at a time of transition.Typically, palliative care has offered a holistic, non-curative focus with an emphasis on improving the quality of life of people with life-limiting conditions. Traditionally it has aimed to improve the conditions of people who were dying of cancer. Palliative care now seeks to extend a holistic, team-based and family-centred approach to people with other life-limiting conditions. Until now the degree to which this aim was reflected in the actual provision of health services has been unclear. There has been a paucity of population-based data on which to base equitable healthcare decision-making regarding the extension of palliative care topeople suffering from a range of life-limiting, complex and painful conditions. Our study provides such data for Western Australia and provides an insight into who is missing out on palliative care services in the last year of life.